Kajian Teknis Penerangan Bengkel Produksi Kapal Perang Di PT. PAL Indonesia - Wahyu Ramadhan Cahaya Firdaus; Aris Heri Andriawan (Pusat Riset dan Inovasi Nasional, 2023)
PAL Indonesia is one of the construction companies in the maritime industry that focuses on producing above and below the surface ships which the Indonesian government highly relies on, therefore the safety system there is very strict, including safety lighting. With good lighting, objects can be seen clearly, so that the operation of production equipment and work in the workshop is optimal. However, the company PT. PAL Indonesia has a problem, namely in the warship production workshop, workers often complain because the lighting in the workshop is not bright enough, which causes workers to experience red, watery and sore eyes. Therefore, researchers are interested in analyzing whether the existing lighting standard is in accordance with SNI 03-6197-2000, namely 350lux. From the research that has been done, it is found that the PT PAL workshop with an area of 2700m2 has an average light intensity measurement of 82.22lux, so re-planning is needed to produce a light intensity that is in accordance with the standards. Based on the results of calculations according to standards, 42 light points are obtained with an average lighting of 354 lux which is simulated using the dialux application. The addition of these light points had an impact on increasing electricity bill rates, which were initially IDR 624,575.34 per month to IDR 2,186,013.69 per month.